Knitting with nature: a chronicle of South Africa's biomes, told through Melville Koppies' Visitors Centre - Reitmann, Liezel (My University, 2021)
South Africa is rich with a vast, incredible and unique heterogeneity of flora, one of the largest collections in the world. South Africa displays nine different terrestrial Biomes, amongst which two are unique and exclusive to the country. These are the iconic Western Cape Fynbos and the Northern Cape Succulent Karoo the latter of which is known for the annual blooming flowers of Namaqualand. This makes South Africa one of the world’s megadiverse countries and is thus as a nation in which conservation efforts must become a high priority. Therefore, significant efforts should be placed on educating the general public as to South Africa’s natural importance, and ideas on how to utilize its national resources identified and implemented. The connection between nature, people and the built environment has been a hot topic for many years within various disciplines. Arguments presented through the philosophy of phenomenology, the hypothesis of Biophilia, and the principles found in Biomimicry have proven that this connection can provide an increase in the health and well-being of both people and our natural environment in a sustainable way. This is further proof of the importance of the conservation of our natural world, particularly within our urban context where the relationship between nature, people and buildings are the strongest. The question then arises: How can South Africa’s treasured biodiversity be utilized and expressed spatially to highlight the importance of the protection of our natural environment, particularly that found within an urban context, by knitting people and nature together through the functions of education, recreation and conservation? The MELVILLE KOPPIES VISITOR CENTRE provides a possible solution to this question. It does so by aiming to function as a driver for the conservation and celebration of our national natural treasure; acting as a place of connection and healing; being a vehicle for education and the inspiration for the future creation of innovative, responsible and sustainable developments; and illustrating the importance of urban ecosystems. This will potentially bring with it tourism, local and foreign investment, job opportunities, sustainability, and increased global awareness of, and responsibility towards, the natural environment
A design project submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) July 2021